2020
DOI: 10.1155/2020/8880107
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on High-Energy and Low-Energy Microfracture Event Evolution Characteristics in the Development Process of Rock Failure

Abstract: The evolution characteristics of high-energy and low-energy microfracture events play an important role in the brittle failure mechanism of rock and reasonable microseismic (MS) monitoring and acoustic emission (AE) monitoring. The bimodal distribution (BMD) model is commonly used to observe the evolution characteristics of high-energy and low-energy MS events; however, its precise mechanism remains unclear. The evolution characteristics of high-energy and low-energy microfracture events are assessed in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For example, the deformation and failure characteristics of strong–weak coupling structures with different height ratios (HRs) under the disturbance of periodic mining stress is still unclear. The coal roadway is subject to periodic stress disturbance during working face mining, resulting in deformation, damage, and even failure, , and the instability and damage of the roadway are the prerequisites for the occurrence of outbursts in mining . The layout parameters of the strong and weak zones may directly affect the overall failure process of the strong–weak coupling structures and thus influence the outburst prevention effect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the deformation and failure characteristics of strong–weak coupling structures with different height ratios (HRs) under the disturbance of periodic mining stress is still unclear. The coal roadway is subject to periodic stress disturbance during working face mining, resulting in deformation, damage, and even failure, , and the instability and damage of the roadway are the prerequisites for the occurrence of outbursts in mining . The layout parameters of the strong and weak zones may directly affect the overall failure process of the strong–weak coupling structures and thus influence the outburst prevention effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ma, C. C. efficiently interpreted progressive rupture effects in microseismic event clusters by feeding microseismic information into numerical simulations [7]. Yu, G. F. found that the high-energy microseismic events at Dongjiahe coal mine LW22517 were generated by the increased scale of overburden destruction as the insufficient mining stage entered the sufficient mining stage [23]. Pang Huan-dong inferred that micro-earthquake phenomena in the coal mine production site are mainly caused by shear action [24].…”
Section: Introductionmentioning
confidence: 99%
“…The coal-rock composite system is accompanied by energy accumulation, transformation, and release in the process of damage and failure (Yu et al, 2020;Liu et al, 2019;Pan et al, 2020;Gao et al, 2020). Therefore, studying the characteristic of energy and damage of the coal-rock composite system under cyclic loading is of great significance to preventing coal mine disasters.…”
Section: Introductionmentioning
confidence: 99%